THE EFFECTIVENESS OF ROLE-PLAYING LEARNING METHOD IN IMPROVING THE MASTERY OF ARABIC VOCABULARY IN SPEAKING SKILLS OF STUDENTS OF CLASS VII MTsN I MAKASSAR - Ghifari, Ahmad; Syihabuddin, Syihabuddin; Sopian, Asep (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
The problem in this study is the low mastery of Arabic vocabulary in MTsN I Makassar students. This study aims to improve the skill of Arabic vocabulary through a role-playing learning method in class VII students of MTsN I Makassar. This research uses qualitative methods with a type of classroom action research consisting of four stages: action planning, action implementation, observation, and reflection, carried out in two cycles. The results showed: (1) Arabic language learning through the role playing method carried out through nine stages starting from providing motivation to students, providing voluntary opportunities to become actors, arranging the stages of the cast, preparing observers, carrying out their respective roles, discussion and evaluation, then re-enactment, followed by the second stage of evaluation, and finally helping students to gain valuable experience in their lives through interactional activities with their friends; (2) Students' Arabic vocabulary after using the role playing learning method showed a score in the average category of sufficient in first cycle with an average score of 71.7 and an excellent average category in second cycle with an average score of 80.5 which was marked by an increase in the number of vocabulary mastered and their pronunciation during role playing from first cycle to second; (3) The increase in students' vocabulary through the application of the role playing method can be seen in the increase in the assessment category from first cycle by obtaining an average score of 71.7 with a sufficient category, the percentage of completeness reached 52.5% with a total of 21 students. The implementation of the second cycle has an average score of 80.5 with a good category; the percentage of completeness is 80.5%, with a total of 35 students.